A Fungal Consortium Mitigating Arsenic Uptake In Rice Under Cultivation In Arsenic- Contaminated Soil (International Journal of Food and Nutritional Sciences, 2022)
A total of fifteen novel arsenic tolerant soil fungal strains were isolated from the paddy fields of West Bengal, India and were checked and approved for producing a marked decline in the amount of arsenic present in our previous study. In our present study, four leading strains out of those fifteen showing excellent arsenic removal potential were selected for developing a talc-based soil fungal consortia formulation with extended shelf life and creating a bio-inoculant arsenic remediation package for their soil applications and field trials. Initially, plant growth promoting potentials and compatibility characterization was performed to see the stimulating and inhibitory effects respectively. For establishing talc as the most suitable carrier in the field, a pot experiment was set up using a rice variety sarjoo-52 treated with carrier-based inoculum of the strains. Talc was established as the best carrier augmenting the desired fungal formulation. The shelf-life study was conducted and these formulations were found viable for a period of 180 days. The log mean value these of these formulations increased with further addition of enrichment additives. Out of the total additives checked for growth promotion abilities in broth, sucrose and CaCO3 at a concentration of 0.5% gave the best results and improvised the shelf life of the formulation. These fungi serve a dual purpose in amelioration of arsenic uptake by the rice plants along with their excellent roles in plant growth promotion. The carrier-based approach will further increase the durability of the formulated product and nullifying/reducing arsenic toxicity will help in gaining a better yield. The purpose of the work is to produce a preparation of a microbial formulation containing live fungi for the removal of arsenic, and plant growth promotion in crops grown in arsenic- contaminated fields. The study focussed on producing a fungal consortium formulation comprising of four novel strains namely Westerdykella aurantiaca (FNBR-FA 03), Trichoderma longibrachiatum (FNBR-FA 06), Lasiodiplodia sp. (FNBR-FA 13), Rhizopus delemer (FNBR-FA 19). The preparation is having synergistic effects on arsenic amelioration. This fungal formulation has enhanced efficiency and is a stable delivery system, which is cost-effective and commercially viable.